2017
DOI: 10.3892/or.2017.5924
|View full text |Cite
|
Sign up to set email alerts
|

miR-217 targeting DKK1 promotes cancer stem cell properties via activation of the Wnt signaling pathway in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies and exhibits heterogeneity in terms of clinical outcomes and biological activities. Emerging evidence has demonstrated that cancer stem cells (CSCs) play important roles in the tumorigenesis and progression of HCC. However, the molecular mechanisms underlying the stemness maintenance of CSCs remain largely unknown. In the present study, through real-time PCR, western blotting, luciferase assays, RNA immunoprecipitation, and in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…qRT-PCR results showed that the expression of miR-217 was negatively correlated with the expression of RMRP ( Figure 6B), which was consistent with the above sequencing results. can participate in tumor progression partially by regulating DKK1, 15,16 we also detected expression of DKK1, Bmi1, CD44…”
Section: Rna Component Of Mitochondrial Rna Processing Endoribonuclmentioning
confidence: 76%
See 1 more Smart Citation
“…qRT-PCR results showed that the expression of miR-217 was negatively correlated with the expression of RMRP ( Figure 6B), which was consistent with the above sequencing results. can participate in tumor progression partially by regulating DKK1, 15,16 we also detected expression of DKK1, Bmi1, CD44…”
Section: Rna Component Of Mitochondrial Rna Processing Endoribonuclmentioning
confidence: 76%
“…Subsequently, we transfected miR‐217 mimics into HCCC‐9810 overexpressing RMRP (Figure A) and found that re‐upregulation of miR‐217 expression can rescue the cancer‐promoting effects of overexpression of RMRP (Figure D,E). Because GO and KEGG analysis based on downstream miRNA expression profiles of RMRP focused the function of RMRP on stem cell‐related characteristics, and previous studies of Jiang et al and Dai et al showed that miR‐217 can participate in tumor progression partially by regulating DKK1, we also detected expression of DKK1, Bmi1, CD44 and CD24 in HCCC‐9810 cells after RMRP knockdown. qRT‐PCR results showed that DKK1, Bmi1 and CD24 expression were downregulated but expression of CD44 remained unchanged (Figure ).…”
Section: Resultsmentioning
confidence: 91%
“…In the HCC cell lines HepG2 and Huh7, miR-217 acts as oncogenic miRNA to enhance stem cell markers' expression and promote tumorsphere formation by suppressing the expression of DKK1, a Wnt antagonist, leading to hyperactivation of the Wnt/β-catenin pathway [132].…”
Section: Mir-217mentioning
confidence: 99%
“…(Li et al 2015) However, miR-217 was also found to be overexpressed in HCC and is potentially involved in promoting hepatic disease. (Jiang et al 2017) miR-217 induces cancer stem cell-like phenotypes resulting in the activation of the Wnt pathway in HCC cells. (Jiang et al 2017) High miR-217 levels leads to fat deposition in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…(Jiang et al 2017) miR-217 induces cancer stem cell-like phenotypes resulting in the activation of the Wnt pathway in HCC cells. (Jiang et al 2017) High miR-217 levels leads to fat deposition in hepatocytes. (Yin et al 2012) These conflicting results may be attributed to the difference in the cell lines used in the experiments and the different stages of the disease when the studies were conducted.…”
Section: Discussionmentioning
confidence: 99%